Recent Trends in the Antidiabetic Prominence of Natural and Synthetic Analogues of Aurones - Rammohan Aluru; Anindita Mukherjee; Grigory V. Zyryanov; Adinath Majee; Sougata Santra (Current Issues in Molecular Biology, 2023)
Natural products are a boundless source for the development of pharmaceutical agents against a wide range of human diseases. Accordingly, naturally occurring aurones possess various biological benefits, such as anticancer, antioxidant, antimicrobial, antidiabetic, anti-inflammatory, antiviral and neuroprotective effects. In addition, various studies have revealed that aurones are potential templates for the regulation of diabetes mellitus and its associated complications. Likewise, certain aurones and their analogues have been found to be remarkable kinase inhibitors of DARK2, PPAR-γ, PTPM1, AGE, α-amylase and α-glucosidase, which represents a promising approach for the treatment of chronic metabolic disorders such as diabetes. Therefore, in our present study, we provide a detailed account of the advances in aurones as antidiabetic agents over the past decade.